Interactive Learning Media at Yaspa Kindergarten Palembang - Mawardah, Mutia; Arisca, Noca (Institut Teknologi dan Bisnis Asia Malang, 2025)
Purpose: Learning media play a crucial role in the educational process, especially for early childhood learners in kindergarten. These media support the development of various aspects of a child’s growth, including motor skills, language, moral values, social-emotional well-being, cognition, and artistic expression. Young children learn most effectively through play and interaction with engaging and easy-to-understand media. Method: The method used is observation to examine the phenomenon, followed by the implementation of interactive learning an approach to the teaching and learning process that emphasizes the active involvement of students through two-way interactions between students and teachers, among students, and between students and learning media. The goal of interactive learning is to create a dynamic, participatory, enjoyable, and meaningful learning environment, so that students are not merely passive recipients of information, but also take an active role in constructing their own understanding. Practical Applications: The interactive learning implemented at YASPA Kindergarten Palembang through various media such as pasting and cutting, drawing and storytelling, counting using puzzles, reading applications, block play, and paper sewing contributes significantly to early childhood development. Conclusion: Based on the internship at YASPA Kindergarten Palembang regarding the implementation of interactive learning media for early childhood, it can be concluded that the use of various interactive media such as scrapbook, picture sequence cards, number puzzles, letter cards, building blocks, and paper sewing activities is highly effective in enhancing children's engagement, creativity, as well as cognitive and motor skills.